2014
DOI: 10.1007/s10597-014-9818-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Burnout Among Nurses in Taiwan

Abstract: Nurse burnout is a crucial issue for health care professionals and impacts nurse turnover and nursing shortages. Individual and situational factors are related to nurse burnout with predictors of burnout differing among cultures and health care systems. The predictors of nurse burnout in Asia, particularly Taiwan, are unknown. The purpose of this study was to investigate the predictors of burnout among a national sample of nurses in Taiwan. A secondary data analysis of a nationwide database investigated the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 29 publications
3
53
0
6
Order By: Relevance
“…Queiros et al [36] reported that DP was related to individual age and gender while job rank (senior or junior) and length of working experience were significantly associated with poor sense of PA. In other studies, EE was associated with age and education level [37] and unmarried nurses had high scores of EE and DP and low score of PA. [16] Ang et al [15] also found that age, job rank, and neuroticism were significantly related to EE, DP, and PA.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Queiros et al [36] reported that DP was related to individual age and gender while job rank (senior or junior) and length of working experience were significantly associated with poor sense of PA. In other studies, EE was associated with age and education level [37] and unmarried nurses had high scores of EE and DP and low score of PA. [16] Ang et al [15] also found that age, job rank, and neuroticism were significantly related to EE, DP, and PA.…”
Section: Discussionmentioning
confidence: 96%
“…[14] Moreover, it can be related to nurse shortages in diverse clinical settings. [15][16][17] Burnout has a wide range of symptoms; [17] however, it can be conceptualized into three categories: emotional exhaustion (EE), depersonalization (DP), and reduced personal accomplishment (PA). [18] Emotional exhaustion refers to feelings of being overwhelmed; depersonalization is defined as impersonal feelings that seem unreal or not belonging to oneself; while reduced personal accomplishment means a lack of self-achievement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Medidas encaminadas al desarrollo de este sentimiento de justicia serían la implementación de modelos de liderazgo (28) o la orientación hacia los objetivos (29) . Del mismo modo que en estudios previos (18,30) se observa que la edad de los profesionales, la sintomatología física o enfermedades crónicas, y el estado civil influyen en el engagement y en el síndrome de burnout en el presente estudio. Las relaciones de las sub-escalas que componen el engagement con la situación laboral del cónyuge no ha sido analizada en los estudio consultados, pero su asociación parece lógica debido al estrés psicosocial que esta situación puede generar.…”
Section: Discussionunclassified
“…Entre estos cuestionarios se encuentran el Gallup Q12 (12) , el cuestionario del Engagement Personal (13) , el Utrecht Work Engagement Scale (UWES) (14) , y el Cuestionario de Seis Áreas de la Vida Laboral (Areas of WorklifeScale (AWS) (15) , validado al castellano por Gascón (16) . Conseguir profesionales con un alto nivel de "engagement" es el objetivo de las organizaciones laborales, conocer cuáles son las variables personales, sociodemográficas y laborales que se asocian a él permite desarrollar estrategias que promuevan su desarrollo entre los profesionales y evitar todas aquellas que promuevan el desarrollo del síndrome de burnout (17,18) por lo que el objetivo del presente estudio es conocer la situación del engagement en los profesionales sanitarios de los centros sanitarios de una zona del noreste de España, así como las variables personales, socio-demográficas y laborales que se asocian a él.…”
Section: Nº 47 Julio 2017unclassified
See 1 more Smart Citation